Empirical modeling and optimization of the flotation of zinc II - Tan, Raymond Girard R. (Animo Repository, 1998)
The removal of dissolved zinc by continuous-mode ion flotation using sodium lauryl sulfate as collector is studied and modeled empirically. A bench-scale flotation cell operating under conditions analogous to those of a single equilibrium stage was used to treat a simulated effluent containing dissolved zinc chloride. Zinc concentrations ranging from 10 - 20 mg/l were employed. Process performance variation with collector dosage exhibited the peak characteristic of flotation processes and zinc level reductions of up to 45 percent were observed. Using response surface methodology, two alternative predictor models were derived. Both models were statistically significant. In addition, they were found to be in agreement with a simplified phenomenological framework developed for the process.